Characteristics of the road infrastructure and injurious cyclist crashes resulting in a hospitalisation. (March 2020) - Meuleners, Lynn B.; Fraser, Michelle; Johnson, Marilyn; Stevenson, Mark; Rose, Geoffrey; Oxley, Jennie
Highlights: In-depth study of 100 cyclists injured due to an on-road crash resulting in hospitalisation. 42% of bicycle crashes involved a motor vehicle and 58 % did not involve a motor vehicle. 21% of all crashes involved the cyclist losing control and 18% involved hitting an object. Approximately half of crashes occurred at intersections (51%) and half at midblocks (non-intersections) (49%). Road surface maintenance and removal of hazards could reduce on-road bicycle crashes which do not involve a motor vehicle. Abstract: Faced with the current growth and change to Western Australia's road network as well as the promotion and increased uptake of cycling, further investigation into crash, injury and road infrastructure characteristics is necessary. An in-depth study was conducted of 100 cyclists who were injured due to involvement in a crash that occurred on-road and resulted in an admission to a hospital. Information collected included a researcher-administered questionnaire, crash details from the Integrated Road Information System (IRIS), injury information from the State Trauma Registry and a virtual on-line site inspection. Overall, 42 % of crashes involved a motor vehicle and 58 % did not involve a motor vehicle. Twenty-one percent of all crashes involved cyclist loss of control, 18% were crashes with another cyclist, 18% involved hitting an object and 1% involved a pedestrian. . Bicycle crashes were severely under-reported with only 40 percent reported to the Police. Approximately half of crashes occurred at intersections (51 %) and half at midblock (non-intersection) sites (49 %). Fifty-seven percent of crashes that occurred at intersections involved a motor vehicle, whereas only 27% of crashes that occurred at midblocks involved a motor vehicle. The majority of cyclists' injuries were classified as minor according to the Injury Severity Score with the mean number of body regions injured being 4.5 (SD = 2.2). The mean number of days in hospital care was 5.2 days (SD = 5.6, range: 1–33). These findings can be used to guide road infrastructure treatments that reduce the risk of bicycle crashes in Western Australia and insights may inform action in other jurisdictions where cycling is increasing in popularity.